Significance and Key Challenges in Conducting Stress Testing for Islamic Commercial Banks - Jamshaid Anwar Chattha (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
With the current cross-border growth in Islamic finance, Islamic commercial banks (ICBs) are looking forward to being perceived as an industry in the process of becoming mature. This would require the establishment of some basic infrastructure, including sophisticated risk management tools that enhance the soundness and resilience of the ICBS. This paper focuses on the latter that is the role and significance of stress testing as a risk management tool. The stress testing has become part of the regulatory and supervisory authorities within the financial stability analysis. The global financial crisis (2008) has placed the spotlight squarely on stress tests. Though, ICBs operate within the similar financial environment, and their balance sheet composition, however, calls for different treatment in stress testing. Apart from the specificities of ICBs, there are key issues and challenges that should be given due considerations in developing an appropriate stress testing regime. This paper explores key specificities and challenges. The paper argues that in the beginning, conducting the stress testing may not appear a simple task for the ICBs. However, a proper consideration to the challenges identified in the paper would certainly tend to improve the overall effectiveness and credibility of the stress testing programmes.